2017
DOI: 10.1016/j.rbmo.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural determinants of US women's ethical views on various fertility treatments

Abstract: Ethical concerns over treatments for infertility can discourage patients from pursuing fertility healthcare. This study aims to evaluate the sociocultural factors that influence the ethical views of reproductive-aged women regarding various fertility treatments. A publicly available cross-sectional survey of 4792 nationally representative US women aged 25-52 years was analysed to identify the frequency of ethical concerns over such interventions. Concerns were most common for treatments that increase the chanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Educational level was previously reported as one of the strongest predictors of women's perceptions of the ethics of infertility treatments [12]. This finding is in line with our results, where educational level was significantly related to the participants' attitudes (OR: 2.029, 95% CI: 1.431-2.876, P <0.001).…”
Section: Discussion:-supporting
confidence: 92%
See 1 more Smart Citation
“…Educational level was previously reported as one of the strongest predictors of women's perceptions of the ethics of infertility treatments [12]. This finding is in line with our results, where educational level was significantly related to the participants' attitudes (OR: 2.029, 95% CI: 1.431-2.876, P <0.001).…”
Section: Discussion:-supporting
confidence: 92%
“…On the other hand, age did not appear to be a significant factor [11]. Another study conducted in the Midwest region of United States found that age and education level significantly affected the women's ethical concerns toward ART [12]. Moreover, it was reported that women with a longer length of awareness of ART were significantly more likely to have a favorable attitude toward ART [11].…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Religion is known to be a determinant for attitudes towards the ethics of ART for both healthcare providers (Fonnest et al , 2000) and patients (Power et al , 1990; Genius, 1993; Schenker, 2005; Dutney, 2007; Shreffler et al , 2010; Collins and Chan, 2017); however, little research has explored the nature of and reasons for such views, especially in the Christian faith (Schenker, 2005). Family formation is central to the concerns of the church (Dutney, 2007); therefore, infertility has considerable impact on many Christians.…”
Section: Introductionmentioning
confidence: 99%
“…A person's social milieu also dictates ethical concerns. For example, Collins and Chan (2017) reported that women in the US were concerned about treatment if it increased twinning rates (54%) and involved third-party input (48-51%), although IVF (30%) and partner insemination (14%) were also ethically problematic to some. A number of sociocultural determinants (e.g, being Black) were associated with greater treatment concerns, whereas being Hispanic was associated with concerns about donor eggs, and religiosity predicted concerns about IVF and all third-party AC.…”
Section: The Wider Sociocultural Contextmentioning
confidence: 99%